A prospective longitudinal study investigating outcomes including patient-reported outcome measures after surgery for metastatic bone disease: protocol for the BoMA-PRO multi-centre MBD outcomes study. (15th February 2021) - Downie, Samantha; Stillie, Alison; Moran, Matthew; Sudlow, Catherine; Simpson, A. Hamish R. W.
Abstract : Aims: Surgery is often indicated in patients with metastatic bone disease (MBD) to improve pain and maximize function. Few studies are available which report on clinically meaningful outcomes such as quality of life, function, and pain relief after surgery for MBD. This is the published protocol for the Bone Metastasis Audit — Patient Reported Outcomes (BoMA-PRO) multicentre MBD study. The primary objective is to ascertain patient-reported quality of life at three to 24 months post-surgery for MBD. Methods: This will be a prospective, longitudinal study across six UK orthopaedic centres powered to identify the influence of ten patient variables on quality of life at three months after surgery for MBD. Adult patients managed for bone metastases will be screened by their treating consultant and posted out participant materials. If they opt in to participate, they will receive questionnaire packs at regular intervals from three to 24 months post-surgery and their electronic records will be screened until death or five years from recruitment. The primary outcome is quality of life as measured by the European Organisation for Research and the Treatment of Cancer Quality of Life questionnaire (EORTC-QLQ) C30 questionnaire. The protocol has been approved by the Newcastle & North Tyneside 2 Research Ethics Committee (REC ref 19/NE/0303) and the study is funded by the Royal College of Physicians and Surgeons of Glasgow (RCPSG) and the Association for Cancer Surgery (BASO-ACS). Discussion: This will be the first powered study internationally to investigate patient-reported outcomes after orthopaedic treatment for bone metastases. We will assess quality of life, function, and pain relief at three to 24 months post-surgery and identify which patient variables are significantly associated with a good outcome after MBD treatment. Cite this article: Bone Jt Open 2021;2(2):79–85.